1996
DOI: 10.1177/030098589603300616
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Plasmacytosis in Rabbits: A Histologic and Ultrastructural Study

Abstract: Abstract.A retrospective study revealed intestinal plasmacytosis in 53 of 102 rabbits used in various experimental studies and as controls. The breeds affected included New Zealand white (n = 46), Dutch-belted (n = 6), and Watanabe (n = 1) rabbits. Sex predisposition was not found in any breed. The mean (+ SD) ages were 3.1 I 1.4 years for New Zealand white rabbits, 1.3 +. 1.1 for Dutch-belted rabbits, and 2 years for the Watanabe rabbit. The severity increased with animal age. The incidence was higher ( P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Instead, they had intestinal plasmacytic infiltration similar to lymphocytic-plasmacytic inflammatory bowel disease of dogs and cats (Day et al , 2008). A prior study identified comparable intestinal plasmacytic infiltration in 53 of 102 (52%) rabbits used for various experimental purposes (Li et al , 1996). It is likely that these rabbits had underlying immune-mediated intestinal disease with secondary EPEC infection.…”
Section: Discussionmentioning
confidence: 95%
“…Instead, they had intestinal plasmacytic infiltration similar to lymphocytic-plasmacytic inflammatory bowel disease of dogs and cats (Day et al , 2008). A prior study identified comparable intestinal plasmacytic infiltration in 53 of 102 (52%) rabbits used for various experimental purposes (Li et al , 1996). It is likely that these rabbits had underlying immune-mediated intestinal disease with secondary EPEC infection.…”
Section: Discussionmentioning
confidence: 95%